Circular Medicine – Being Mindful of Resources and Waste Recycling in Healthcare Systems - Syms R; Taylor-Robinson SD; Trovato G (Risk Management and Healthcare Policy, 2023)
Richard Syms,1 Simon D Taylor-Robinson,2 Guglielmo Trovato3 1Department of Electrical and Electronic Engineering, Imperial College London, London, UK; 2Department of Department of Surgery and Cancer at St Mary’s Hospital Campus, Imperial College London, London, UK; 3Faculty of Medicine, University of Catania, Catania, Sicily, ItalyCorrespondence: Simon D Taylor-Robinson, Department of Department of Surgery and Cancer, Imperial College London, St Mary’s Hospital Campus, London, W2 1NY, United Kingdom, Fax +442037249369, Email str338333@gmail.comAbstract: In the light of the COP27 Climate Change Conference, the concept of the circular economy has come to the fore with promotion of reuse and recycling of appliances and materials from electronics to clothes. This concept has not been widely taken up by healthcare systems. In this perspective article, we discuss the idea of the circular economy and how, by extension, the concept of “circular medicine” with optimised hospital and medical clinic waste recycling might be promoted in the context of better stewardship of resources in healthcare management.Keywords: circular economy, recycling, climate change